Tinjauan Yuridis terhadap Penerapan Pasal 359 KUHP dalam Kasus Kematian Mahasiswa IAIN Gorontalo - Alim Aljufri, Syah; Y. Imran, Suwitno; A Arief, Supriyadi (Cv. Kalimasada Group, 2025)
The case of the death of a student at IAIN Sultan Amai Gorontalo due to cadre training has raised legal problems related to the application of Article 359 of the Criminal Code, which is considered less appropriate than Article 354 of the Criminal Code. This study aims to examine the legal investigation in the application of Article 359 of the Criminal Code (KUHP) against five suspects in the case of the death of a student at IAIN Sultan Amai Gorontalo which occurred during a cadre training activity by a student organization. This study uses an empirical method with a qualitative approach, which relies on primary data in the form of interviews with investigators and secondary data from official documents and trial facts. The preparation of Article 359 of the Criminal Code after conducting a case title with the prosecutor's office with the consideration that the violence that occurred was only in the form of selling using sandals, so it was deemed not to fulfill the elements of seriousness. In addition, other considerations include the condition of the victim who was already sick, the negligence of the committee in providing first aid, not immediately taking the victim to the hospital, and the absence of professional medical personnel during the activity. However, the trial facts indicate that there was real, systematic, and fatal physical violence against the victim, as evidenced by witness testimony and the results of a medical autopsy. Therefore, the application of Article 359 of the Criminal Code in this case raises legal problems because there are strong indications that the element of serious assault as regulated in Article 354 of the Criminal Code is more appropriate to be applied. This study emphasizes the importance of thoroughness and professionalism of investigators in determining the construction of articles based on complete legal facts, as well as the need for a law enforcement approach that reflects substantive justice for the victim and their family.